Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1365-2958.1997.4321788.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Porphyromonas gingivalis to matrix proteins via a fimbrial cryptic receptor exposed by its own arginine‐specific protease

Abstract: SummaryPorphyromonas gingivalis, a Gram-negative anaerobe, is known to be involved in the pathogenesis of periodontitis. P. gingivalis fimbriae, which are proteinaceous appendages extending from the cell surface, may contribute to the adherence of the organism to the host cell surface. We previously suggested that arginine-specific protease produced by P. gingivalis enhanced the adherence of purified fimbriae to fibroblasts or matrix proteins. In this study, we have revealed the mechanism of the enhanced bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 40 publications
4
54
0
Order By: Relevance
“…Considered together, these results suggest that the Arg-and/or Lys-specific proteinases may mediate adherence through cleaving hidden or latent surface receptors on MRC-5 cells to which the RgpA-Kgp complexes then adhere through their adhesin domains. This mechanism is similar to that previously described for P. gingivalis W50 adherence to fibronectin (Kontani et al, 1997) and epithelial cells (Pathirana et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Considered together, these results suggest that the Arg-and/or Lys-specific proteinases may mediate adherence through cleaving hidden or latent surface receptors on MRC-5 cells to which the RgpA-Kgp complexes then adhere through their adhesin domains. This mechanism is similar to that previously described for P. gingivalis W50 adherence to fibronectin (Kontani et al, 1997) and epithelial cells (Pathirana et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…To invade host cells that are not professional phagocytes, pathogens utilize diverse molecules and strategies. It has been suggested that functional epitopes of cellular receptors of P. gingivalis are cryptic, and that bacterial protease expose them [24]. The ability of various bacteria in the microbial complex of the gingival sulcus to express surface molecules to specifically interact with other bacterial species and host cells has been suggested to be a critical determinant in plaque formation and structure [19].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular bacterial proteases from a number of pathogenic organisms have been demonstrated to play important roles in virulence. By degrading host tissue substrates like collagen, fibronectin and proteinaceous receptors, these enzymes can destroy host mucosal or skin barriers (Hase & Finkelstein, 1993) and promote pathogen colonization (Kontani et al, 1997). By degrading immunoglobulin or serum complement components, they may also avoid the host immune response (Hase & Finkelstein, 1993).…”
Section: Discussionmentioning
confidence: 99%